2023
DOI: 10.1371/journal.pone.0284128
|View full text |Cite
|
Sign up to set email alerts
|

Where are the data linking infant outcomes, breastfeeding and medicine exposure? A systematic scoping review

Abstract: Introduction Information on the impact of medicines on breastfeeding and the breastfed infant remains scarce. The aims of this review were to identify databases and cohorts holding this information, and pinpoint current information and research deficits. Method We searched 12 electronic databases, including PubMed/ Medline and Scopus, using a combination of controlled vocabulary (MeSH terms) and free text terms. We included studies reporting data from databases with information on breastfeeding, medicines ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
(235 reference statements)
0
1
0
Order By: Relevance
“…By accounting for all the items listed above, researchers increase the likelihood that the only remaining plausible explanation for harm identified is the prescribed medicine. We made no recommendation in relation to breastfeeding, because no studies reported drug utilization during or preceding breastfeeding: very few databases hold data on breastfeeding [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…By accounting for all the items listed above, researchers increase the likelihood that the only remaining plausible explanation for harm identified is the prescribed medicine. We made no recommendation in relation to breastfeeding, because no studies reported drug utilization during or preceding breastfeeding: very few databases hold data on breastfeeding [ 29 ].…”
Section: Discussionmentioning
confidence: 99%